2023
DOI: 10.1186/s12864-023-09436-9
|View full text |Cite
|
Sign up to set email alerts
|

Gene co-expression network analysis identifies hub genes associated with different tolerance under calcium deficiency in two peanut cultivars

Abstract: Background Peanut is an economically-important oilseed crop and needs a large amount of calcium for its normal growth and development. Calcium deficiency usually leads to embryo abortion and subsequent abnormal pod development. Different tolerance to calcium deficiency has been observed between different cultivars, especially between large and small-seed cultivars. Results In order to figure out different molecular mechanisms in defensive responses… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Raw reads were subjected to Trimmomatic software (v0.40) to remove adapters, poly-N-containing reads, and low-quality reads, Q20, Q30, and GC contents of clean data were calculated. The genome of Arachis hypogaea (GenBank accession number GCF_003086295.2_arahy.Tifrunner.gnml.KYV3) was used as a reference sequence [ 15 ], and the clean data were mapped against the reference genome using the software Hisat2 (v2.0.1). Sequences with total mapped reads or fragments larger than 70% of the data were selected for subsequent analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Raw reads were subjected to Trimmomatic software (v0.40) to remove adapters, poly-N-containing reads, and low-quality reads, Q20, Q30, and GC contents of clean data were calculated. The genome of Arachis hypogaea (GenBank accession number GCF_003086295.2_arahy.Tifrunner.gnml.KYV3) was used as a reference sequence [ 15 ], and the clean data were mapped against the reference genome using the software Hisat2 (v2.0.1). Sequences with total mapped reads or fragments larger than 70% of the data were selected for subsequent analysis.…”
Section: Methodsmentioning
confidence: 99%
“…As an important economic and oil crop grown worldwide, peanuts often suffer from abiotic stress, such as drought, salt, and low temperatures [31]. In addition, it is important to note that peanut is a calcium-addicted crop, and calcium (Ca) deficiency can significantly impact the growth and development of the plant, resulting in various physiological changes [32,33]. Previous transcriptomic studies have indicated that Ca 2+ deficiency in soil can lead to the abortion of peanut embryos or prevent kernel expansion, ultimately resulting in reduced peanut yields [34][35][36].…”
Section: Introductionmentioning
confidence: 99%